An Array of Aspects in the Feasibility of Different Concentrated Solar Power Technologies - Balo, Figen; Sua, Lutfu S. (wiley, 2024)
Sustainable power resources are the best alternative to fossil-based fuels as they are renewable and have fewer or no ecologic effects. Sun thermal energy industries are potentially one of the abundant available renewable power resources that could replace the classic fossil fuel energy facilities. Solar concentrator mechanisms utilize mirrors to concentrate and reflect sun rays on a receiver. The power from the concentrated sun rays warms up a high-temperature liquid in the receiver. This warmth-also referred to as heat power-can be used to provide energy to an engine or rotate a turbine to produce electricity. It can also be utilized in various sectoral implementations, such as improved oil recovery, water desalination, food processing, mineral processing, and chemical production. Sun power dish, sun power tower, linear Fresnel reflector, and parabolic trough collector are concentrated solar industries for commercial purposes. Assessment of the weight ratio of the alternatives with the highest thermal efficiency is very significant for business applications. In this study, four different solar concentrator mechanisms are evaluated simultaneously based on ten decision criteria by constructing a hierarchical structure of the criteria. The applied methodology and the structure are aimed to provide a basis for feasibility studies in the field. © 2024 Scrivener Publishing LLC.
Keywords: Concentrated solar energy; renewable energy; solar power